2000 10th Mediterranean Electrotechnical Conference. Information Technology and Electrotechnology for the Mediterranean Countri
DOI: 10.1109/melcon.2000.879986
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sound stream characterization for reliable, real-time occurrence monitoring of given sound-prints

Abstract: The identification in real-time streaming data using plain template-matching algorithms is difficult due to the undefined frame position in the on-line data compared to the frame-based features' position of the templates. We have investigated the use of the short-time Fourier-spectrum, the short-time Walsh-rpectrum and the short-time signal energy and the ratio of tbe succeeding features from the frame-shift point of view. The last two features aim to improve calculation s p e d in larger set of records. For f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Some other transforms have been proposed: the Discrete Cosine Transform (DCT), the Haar Transform or the Walsh-Hadamard Transform [2]. Richly et al did a comparison of the DFT and the Walsh-Hadamard Transform that revealed that the DFT is generally less sensitive to shifting [20]. The Modulated Complex Transform (MCLT) used by Mihçak et al [5] and also by Burges et al [21] exhibits approximate shift invariance properties [5].…”
Section: Linear Transforms: Spectral Estimatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Some other transforms have been proposed: the Discrete Cosine Transform (DCT), the Haar Transform or the Walsh-Hadamard Transform [2]. Richly et al did a comparison of the DFT and the Walsh-Hadamard Transform that revealed that the DFT is generally less sensitive to shifting [20]. The Modulated Complex Transform (MCLT) used by Mihçak et al [5] and also by Burges et al [21] exhibits approximate shift invariance properties [5].…”
Section: Linear Transforms: Spectral Estimatesmentioning
confidence: 99%
“…It is quite common to apply a very low resolution quantization to the features: ternary [20] or binary [4,19]. The purpose of quantization is to gain robustness against distortions [4,19], normalize [20], ease hardware implementations, reduce the memory requirements and for convenience in subsequent parts of the system.…”
Section: Post-processingmentioning
confidence: 99%
See 2 more Smart Citations